2019
DOI: 10.1002/chir.23107
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective hydrogenation of α‐ketoesters catalyzed by cinchona alkaloid stabilized Rh nanoparticles in ionic liquid

Abstract: The heterogeneous enantioselective hydrogenation of α-ketoesters catalyzed by rhodium nanoparticles (Rh NPs) in ionic liquid was studied with the stabilization and modification of cinchona alkaloids. TEM characterization showed that well-dispersed Rh NPs of about 1.96 nm were obtained in ionic liquid. The results showed that cinchona alkaloids not only had good enantiodifferentiating ability but also accelerated the catalytic reaction.Under the optimum reaction conditions, the enantiomeric excess in ethyl benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…[13] For all these catalysts, ILs have been widely studied for its structure tunability and thermal stability, which therefore have many applications in various fields, such as oxidation, [14] cycloaddition, [15] alkylation, [16] hydrogenation. [17] Furthermore, designing ILs with specific structures of cations and anions can promote cycloaddition effectively and ideally. Chen et al [18] employed amine-functionalized ILs to produce cyclic carbonate and found that the ring-opening process was the rate-limiting step.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] For all these catalysts, ILs have been widely studied for its structure tunability and thermal stability, which therefore have many applications in various fields, such as oxidation, [14] cycloaddition, [15] alkylation, [16] hydrogenation. [17] Furthermore, designing ILs with specific structures of cations and anions can promote cycloaddition effectively and ideally. Chen et al [18] employed amine-functionalized ILs to produce cyclic carbonate and found that the ring-opening process was the rate-limiting step.…”
Section: Introductionmentioning
confidence: 99%
“…There are a multitude of catalysts that are investigated for cycloaddition, such as metal complexes, [9] metal‐organic frame material, [10] hydrogen bond donors, [11] ILs [12] and nonmetallic material [13] . For all these catalysts, ILs have been widely studied for its structure tunability and thermal stability, which therefore have many applications in various fields, such as oxidation, [14] cycloaddition, [15] alkylation, [16] hydrogenation [17] . Furthermore, designing ILs with specific structures of cations and anions can promote cycloaddition effectively and ideally.…”
Section: Introductionmentioning
confidence: 99%
“…Supported noble metal catalysts have shown potential for applications in the asymmetric hydrogenation of CO and CC bonds. In particular, cinchona-modified Pt catalysts supported on high-surface-area materials have been extensively studied for the enantioselective hydrogenation of α-keto esters, owing to their high enantioselectivity (Scheme ). In these catalytic systems, cinchona alkaloids, including cinchonidine (CD), act as chiral modifiers to bestow chirality to the active metal surface.…”
Section: Introductionmentioning
confidence: 99%